2012
DOI: 10.1128/aac.00072-12
|View full text |Cite
|
Sign up to set email alerts
|

Combination Antimicrobial Susceptibility Testing of Multidrug-Resistant Stenotrophomonas maltophilia from Cystic Fibrosis Patients

Abstract: Stenotrophomonas maltophilia is increasingly being isolated from the respiratory tract of individuals with cystic fibrosis, and, because of its multidrug-resistant nature, the selection of suitable treatment regimens can be problematical. Etest methodology was used to facilitate MIC and antimicrobial combination testing on 80 isolates of S. maltophilia cultured from the respiratory tract of Scottish individuals with cystic fibrosis between 2001 and 2010. The overall rate of susceptibility for the 1,410 MIC tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 30 publications
(50 reference statements)
1
34
0
1
Order By: Relevance
“…Community-acquired S. maltophilia infections, especially in the high-risk populations mentioned, have been reported (5), and recently, a communityacquired skin infection was reported for the first time in an immunocompetent individual (6). The multidrug-resistant nature of S. maltophilia makes treatment of infections highly difficult (7), and in recent years, an increased resistance to the preferred antibiotic trimethoprim-sulfamethoxazole has been reported (8)(9)(10). These findings emphasize the need to better understand the virulence mechanisms employed by S. maltophilia.…”
mentioning
confidence: 89%
“…Community-acquired S. maltophilia infections, especially in the high-risk populations mentioned, have been reported (5), and recently, a communityacquired skin infection was reported for the first time in an immunocompetent individual (6). The multidrug-resistant nature of S. maltophilia makes treatment of infections highly difficult (7), and in recent years, an increased resistance to the preferred antibiotic trimethoprim-sulfamethoxazole has been reported (8)(9)(10). These findings emphasize the need to better understand the virulence mechanisms employed by S. maltophilia.…”
mentioning
confidence: 89%
“…Several studies tested in vitro antibiotic combinations on SXT-susceptible S. maltophilia isolates, but only few ones focused on SXT-resistant ones [21]. By different methods, a lot of synergistic combinations were described; including those we tested [8,11,[22][23][24][25]. According to our results, synergy is strain dependent.…”
Section: Discussionmentioning
confidence: 92%
“…Resistance rates of SXT ranges from 2 to 10% globally; however studies from Turkey (15%), Spain (27%), Taiwan (25%) and China (30-48%) reported higher resistance rates [4,[6][7][8]. In patients suffering from cystic fi brosis (CF), the frequency of SXT-resistant S. maltophilia is higher (24-84%) [2,[9][10][11]. Resistance level of isolates from patients with cancer and those treated in intensive care unit (ICU) might be also higher [4].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-drug susceptibility tests do not only give results for susceptibility, but also qualifies the activity of the combined anti-infective agents [11].…”
Section: Resultsmentioning
confidence: 99%